10.1016/s1558-0164(08)70396-1 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Two pulsed field ablation (PFA) catheter systems for atrial fibrillation (AF) are widely adopted: the Affera Sphere-9 (Medtronic) and the Varipulse (Biosense Webster). Their comparative real-world safety is unknown. METHODS: We searched the FDA MAUDE database (June 27, 2026) for all reports naming either catheter since U.S. release. After excluding duplicates and non-catheter components, 743 Affera and 361 Varipulse reports remained. Reports were classified by FDA Event Type (device- vs. patient-related) and complication status, with complications grouped by organ system. Proportions were compared with chi-square or Fisher exact tests in R 4.3.3. RESULTS: Neurologic events were far more frequent among Varipulse reports (44.3 % vs. 14.8%; P < 0.001), driven by stroke (38.0% vs. 9.7%; P < 0.001). Cardiovascular events predominated among Affera reports (43.2% vs. 29.1%; P < 0.001), including ventricular fibrillation (52 vs. 1), heart block (8.7% vs. 1.4%; P < 0.001), and hypotension (5.5% vs. 0.8%; P<0.001); effusion/tamponade was more frequent with Varipulse (15.2% vs. 9.0%; P = 0.003). Complication-free reports were more frequent with Affera (35.3% vs. 21.1%; P < 0.001). Deaths did not differ (2.6% vs 1.4%; P = 0.30). CONCLUSIONS: These PFA systems show distinct reported safety signatures: neurologic/stroke-predominant for Varipulse and cardiovascular/arrhythmic (ventricular fibrillation, heart block) for Affera. Because MAUDE lacks procedural denominators, these proportions describe reported events, not incidence. Prospective, patient-level studies are needed to establish causation.